2005
DOI: 10.1111/j.1467-985x.2005.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey Response and Survey Characteristics: Microlevel Evidence from the European Community Household Panel

Abstract: Summary. Social surveys are usually affected by item and unit non-response. Since it is unlikely that a sample of respondents is a random sample, social scientists should take the missing data problem into account in their empirical analyses. Typically, survey methodologists try to simplify the work of data users by 'completing' the data, filling the missing variables through imputation. The aim of the paper is to give data users some guidelines on how to assess the effects of imputation on their microlevel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 15 publications
6
77
0
1
Order By: Relevance
“…It has been shown that individuals that participate in the first wave of survey panels are more likely to continue participating. It is also reasonable to believe that those individuals answering a self-administered questionnaire, a telephone or a proxy interview as opposed to a face-to-face personal interview might be less interested in the survey project or have less time for it and therefore may be less likely to be retained in the future (see, Nicoletti and Peracchi 2005, and references therein). Coefficients in Table 6 show this is actually the case.…”
Section: The Modelmentioning
confidence: 99%
“…It has been shown that individuals that participate in the first wave of survey panels are more likely to continue participating. It is also reasonable to believe that those individuals answering a self-administered questionnaire, a telephone or a proxy interview as opposed to a face-to-face personal interview might be less interested in the survey project or have less time for it and therefore may be less likely to be retained in the future (see, Nicoletti and Peracchi 2005, and references therein). Coefficients in Table 6 show this is actually the case.…”
Section: The Modelmentioning
confidence: 99%
“…This evidence strongly suggests that mortality and worsening health conditions are likely to be the main cause of nonresponses. For a similar approach on the attrition weighting procedure see, among others, Raab et al (2005), Nicoletti and Peracchi (2005) and Vandecasteele and Debels (2007).…”
mentioning
confidence: 99%
“…Often, logistic regression models are used to relate covariates to nonresponse and to compare response rates across subgroups (Axinn et al 2011;Johansson and Klevmarken 2008;Johnson et al 2006;Abraham et al 2006;Little and Vartivarian 2005;Nicoletti and Peracchi 2005;Lepkowsi and Couper 2002;Little 1986;Rosenbaum and Rubin 1983). In many applications, however, classification trees are considered easier to specify and interpret, specifically with regard to interaction effects (Phipps and Toth 2012;Schouten 2007;Schouten and de Nooij 2005).…”
Section: Classification and Ensemble Treesmentioning
confidence: 99%